2018
DOI: 10.1002/cncr.31750
|View full text |Cite
|
Sign up to set email alerts
|

Is surgery for retroperitoneal sarcoma at “low‐volume” hospitals a bad idea?

Abstract: When volume‐outcome associations are being considered, statistical analyses that ignore correlations due to clustering by hospital are invalid and may lead to confidence intervals that are too narrow and P values that are too small. Before any conclusions are drawn about the value of treatment for retroperitoneal sarcoma at a high‐volume hospital, the statistical analysis should adequately address the question of whether volume is a key factor driving center‐to‐center variability in outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…However, it is also possible that the lack of change reflects a lack of referrals to specialized centers. The etiology of the static rate of MVR warrants attention in future studies as this may be a target for increasing both MVR rates and referrals to specialized sarcoma centers with the goal of improving both postoperative morbidity and mortality as well as oncologic outcomes …”
Section: Discussionmentioning
confidence: 99%
“…However, it is also possible that the lack of change reflects a lack of referrals to specialized centers. The etiology of the static rate of MVR warrants attention in future studies as this may be a target for increasing both MVR rates and referrals to specialized sarcoma centers with the goal of improving both postoperative morbidity and mortality as well as oncologic outcomes …”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, highvolume centers may unintentionally select for patients more likely to have favorable outcomes, possibly in part due to socioeconomic factors. Prior authors have discussed that such retrospective studies must be interpreted with caution [10].…”
Section: Introductionmentioning
confidence: 99%
“…A separate editorial also accompanying the article by Keung et al addresses the validity of the statistical analysis as reported, and therefore we will not explore that herein. Although the difference in actual survival numbers may be debatable, the critical point that the overwhelming majority of patients who undergo treatment for a rare disease are treated at LVHs cannot be underemphasized.…”
mentioning
confidence: 99%